2014
DOI: 10.1590/1982-43272458201405
|View full text |Cite
|
Sign up to set email alerts
|

Marital Quality and Attachment: The Mediator Role of Conflict Resolution Styles

Abstract: Certain variables can act as mediators between marital quality, social and emotional aspects of the individuals and their context. The aim of this study was to investigate the role of conflict resolution styles as mediators between attachment styles and marital quality. A total of 214 couples participated in the present study aged between 18 and 75 years, residents in Southern Brazil. Three scales were administered: The Conflict Resolution Style Inventory, Golombok Rust Inventory of Marital State and Adult Att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
31
0
11

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(48 citation statements)
references
References 31 publications
6
31
0
11
Order By: Relevance
“…Question one. The results of this study concerning conflict style and relationship quality confirm previous research findings that demonstrate the negative impact adverse conflict styles have on relationship quality (Gordon & Chen, 2016;Markman, 1991;Scheeren et al, 2014;Sullaway & Christensen, 1983). Specific to the results from the APIM model used in this study, the use of extreme styles of conflict in marriage is significantly associated with poorer reported relationship quality for both men and women.…”
Section: Research Question Findingssupporting
confidence: 84%
See 3 more Smart Citations
“…Question one. The results of this study concerning conflict style and relationship quality confirm previous research findings that demonstrate the negative impact adverse conflict styles have on relationship quality (Gordon & Chen, 2016;Markman, 1991;Scheeren et al, 2014;Sullaway & Christensen, 1983). Specific to the results from the APIM model used in this study, the use of extreme styles of conflict in marriage is significantly associated with poorer reported relationship quality for both men and women.…”
Section: Research Question Findingssupporting
confidence: 84%
“…In an attempt to better understand relationship quality, many researchers have turned their attention to conflict styles. This research has found that conflict is present in most relationships, that resolving conflict increases relationship satisfaction and enhances intimacy, and that difficulties in resolving conflict that arise in unhappy marriages are often due to negative interaction patterns that tend to escalate rather than reduce conflict (Crowley, 2008;Oka et al, 2014;Prager et al, 2015;Scheeren et al, 2014;Watzlawick, Bavelas, & Jackson, 1967). Furthermore, conflict usually occurs when an individual perceives his or her efforts to meet needs and desires in the relationship as being blocked or interrupted by another (Corcoran & Mallinckrodt, 2000).…”
Section: Conflict Styles In Relationshipsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is the inevitable companion of the human relations. Moreover, the conflict may be useful, but this is possible provided that people are willing to cooperate [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%